ADAT BUGIS (MAPPATEKKA DUI’) MENURUT PANDANGAN HUKUM ISLAM - Riswana; Walhidayah (Sipakainge: Inovasi Penelitian, Karya Ilmiah, dan Pengembangan (Islamic Science), 2024)
This research explains the Mappatekka Dui' Tradition which is considered a symbol of appreciation and respect for other people. Giving money or gifts to someone is considered an expression of gratitude and recognition for the services or assistance provided. And Islamic legal views regarding the Mappatekka Dui' Tradition. The problem solving method uses qualitative techniques with observation and interviews. The results obtained state that Mappatekka Dui' is a procession that is often carried out in the context of weddings. This procession marks an agreement between two parties and strengthens social relations and cultural values passed down from generation to generation. The Mapatekka Dui' tradition reviewed in the Al-Urf' method can be said to be a tradition that does not cause damage or harm because this tradition is only a tribute to the eldest sister who was stepped over by her younger sister to step into marriage.